Travel health and pretravel preparation in the patient with inflammatory bowel disease. Issue 1 (22nd April 2015) - Greveson, Kay; Shepherd, Thomas; Mulligan, John P; Hamilton, Mark; Woodward, Sue; Norton, Christine; Murray, Charles
Abstract : Background and aims: Foreign travel for people with inflammatory bowel disease (IBD) carries an increased risk of travel-related morbidity. There is limited research looking specifically at travel-associated health risks and travel preparation in patients with IBD. The aims of this study are to explore the experience of travel, pretravel preparation undertaken by the patient with IBD and examine IBD healthcare professionals' (HCP) confidence at providing travel advice and the content of that advice. Methods: A survey of patients with IBD attending an outpatient clinic with a separate online survey sent to IBD HCPs recruited using regional and international network databases. Results: A total of 132 patients with IBD, Crohn's disease (67/132, 51%), male (60/132, 45%) and 128 HCPs (IBD nurse specialist 113, 88%; IBD physician 15, 12%) completed the questionnaires. IBD affected travel to some extent in 62% (82/132) of patients, and 64% (84/132) had experienced an IBD flare, of whom 64% still travelled overseas during this time. Only 23% (31/132) travellers sought pretravel medical advice and 40% (53/132) obtained travel insurance. Forty-eight per cent of respondents on immunomodulator therapy were unaware of the need to avoid live vaccines. Twenty-seven per cent (34/128) of IBD HCPs are not confident at providing pretravel advice; vaccination advice (54%), obtaining travel insurance (61%) and healthcare abroad (78%) are the areas of most uncertainty. Conclusions: Patients do not seek adequate pretravel advice and consultations for those who do are often deficient. The majority of IBD professionals are not confident to provide comprehensive travel advice. Greater IBD-specific travel education and awareness is needed for both patients with IBD and professionals.